SOME DERIVATIONS ON THE BOUNDS FOR THE ZEROS OF ENTIRE FUNCTIONS BASED ON SLOWLY CHANGING FUNCTIONS - Datta, Sanjib Kumar; Pramanik, Dilip Chandra (Italian Journal of Pure and Applied Mathematics, 2014)
A single valued function of one complex variable which is analytic in the finite complex plane is called an entire function. The purpose of this paper is to establish the bounds for the moduli of zeros of entire functions in the light of slowly changing functions.